Determinants of entrepreneurial intentions among young graduates: Perspectives of push-pull-mooring model - Obinna C. Ojiaku; Anayo D. Nkamnebe; Ireneus C. Nwaizugbo (Journal of Global Entrepreneurship Research, 2018)
The role of entrepreneurship in economic development is increasingly recognized by policymakers and researchers. Entrepreneurship has been advanced as the panacea for youth unemployment and wealth creation. However, studies on the determinants of entrepreneurial intentions have been inconclusive. Building on the push-pull-mooring model from the migration literature as a theoretical framework, this study provides an integrative model for predicting entrepreneurial intentions amongst young graduates. The survey data was drawn from a sample of 288 National Youth Service Corp members (NYSC) in Anambra State, Southeast Nigeria, to test the applicability of the model. The model was tested using Hierarchical regression. The result confirms the predictive ability of the PPM model on entrepreneurial intentions. Specifically, the result reveals that the pull factors (i.e, independence, autonomy, opportunities exploitation e.t.c) and the mooring variables (i.e., government support, personal attitude, self-efficacy e.t.c) significantly influence entrepreneurial intentions with the mooring variables having the most influence. Therefore, the study recommends the need for policy initiatives towards exposing these young graduates to market opportunities through a mentor-protégé arrangement with successful entrepreneurs during the NYSC programme and providing the necessary supports in the form of funding.
Keywords: 650; Entrepreneurship; Entrepreneurial intentions; Push-pull-mooring factors; Migration; Nigeria